Maxillary neoplasms in four dromedary camels - Ibrahim, Abdelazim; Zabady, Mohamed; El Nahas, Ayman; Aljazzar, Ahmed; Al-Hizab, Fahad; Kandeel, Mahmoud; Porter, Brian F. (Frontiers in Veterinary Science, 2023)
Four camels (Camelus dromedarius) presented to the Veterinary Teaching Hospital at King Faisal University with maxillary masses. On radiographs, the masses were multicystic and expanded the maxillary bone. The tumors were diagnosed by histopathologic examination as conventional ameloblastoma, two cases as intraosseous squamous cell carcinoma, and central odontogenic fibroma with ossification. To the authors’ knowledge, this is the first report of ameloblastoma in a camel, the first detailed description of maxillary squamous cell carcinoma in camels, and the first report of central odontogenic fibroma in any animal species.